Life Science Curriculum and Textbooks: The Comparison of Turkey and Russia - Nur ÜTKÜR GÜLLÜHAN; Elvira GUSEINOVA (Anı Publishing, 2021)
This study aimed to investigate the similarities and differences between curriculum and textbook contents of Life Sciences course in Turkey and World Around course in Russia. To that end, curriculum and textbooks of Life Sciences and World Around in effect in both countries in the academic year of 2019-2020 were examined. In the present study, using the intertwined single-case design of qualitative research designs, document review was opted for as the measure. The data achieved were subjected to descriptive content analysis. Codes, categories and themes utilized in the analysis of curriculum and textbooks were shaped in accordance with the contents of curriculum and textbooks in light of similar studies in the literature. Main features of the curriculum and textbooks and how subjects were presented were examined within the framework of activity and assessment practices. Turkish and Russian Life Sciences Curriculum and textbooks were similar overall but had some differences concerning content. Consequently, it was concluded that it would be more relevant to integrate certain activities and methods that would bring the students closer to real life into the Turkish Life Sciences textbooks.